Moisture conversion and migration in single-wheat kernel during isothermal drying process by LF-NMR. Issue 7 (19th May 2019) - Hu, Xuanye; Wu, Ping; Zhang, Shiping; Chen, Sen; Wang, Li
Abstract: Conversion among different moisture-binding types of single Hebei wheat kernels during isothermal drying processing at 60 °C was studied by low field nuclear magnetic resonance (LF-NMR), and moisture migration was studied by MRI. Water inside wheat kernels exists in four types: chemically combined water (T21 ), strong bound water (T22 ), loosely bound water (T23 ), and free water (T24 ). A new method to obtain the contents of different moisture-binding types is forwarded according to the transverse relaxation time distribution curve of dried wheat kernels. Moisture conversion inside wheat kernels during drying occurs mainly through the following mechanisms: high-temperature drives T24 to diffuse to lower moisture areas and transform into other moisture-binding types, and moisture-gradient drives T22 to transform into T24 . The drying process can be divided into two stages. Moisture migrates from endosperm to epidermis during drying. As the drying rate of the wheat kernel significantly decreases, the drying conditions and parameters need to be adjusted to improve the drying rate while ensuring the quality of wheat kernels.